Spontaneous symphysiotomy: rare case review - Choudhary, Ankita; Jhakhar, Rekha; Bhati, Balgopal Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We present here a rare case of spontaneous symphysiotomy. In the case patient came with post-partum hemorrhage with severe pain in groin region, on clinical and pelvic examination there was a gap in pelvic syphysis which further confirmed by pelvic X-ray.